Aliens in medieval law: The origins of modern citizenship - Keechang, Kim (Cambridge University, 2013)
Keechang Kim makes full use of medieval and early modern sources in this original reinterpretation of the legal aspects of feudalism, proposing a radical new understanding of the genesis of the modern legal regime. This innovative study will interest academics, lawyers, and students of legal history, immigration and minority issues.